Metatranscriptomics of microbial biofilm succession on HDPE foil: uncovering plastic-degrading potential in soil communities - Joana MacLean; Alexander Bartholomäus; Roberts Blukis; Susanne Liebner; Dirk Wagner (Environmental Microbiome)
Abstract Background Although plastic pollution is increasing worldwide, very little is known about the microbial processes that take place once plastic debris is incorporated into the soil matrix. In this study, we conducted the first metatranscriptome analysis of polyethylene (PE)-associated biofilm communities in highly polluted landfill soil and compared their gene expression to that of a forest soil community within a 53-day period. Results Our findings indicate that the microbial population present in soil contaminated with plastic debris is predisposed to both inhabit and degrade plastic surfaces. Surprisingly, the microbial community from undisturbed forest soil contained a diverse array of plastic-associated genes (PETase, alkB, etc.), indicating the presence of an enzymatic machinery capable of plastic degradation. Plastic-degrading taxa were upregulated in the early stages of biofilm formation. During the maturation of the biofilm, the alkB1/alkM transcripts, which encode PE-degrading enzymes, and transporters such as fadL, livG, livF, livH, and livM were upregulated, along with transcripts associated with the fatty acid β-oxidation pathway. Conclusions In this study, we address the underlying patterns of gene expression during biofilm development in a PE-associated plastisphere in soil and address the pressing question of whether natural microbial communities have the potential to biodegrade petrochemical-based plastic in the soil environment.